What are the causes of transport insecurity? Results from a survey with transport operators. (April 2016) - Urciuoli, Luca
Abstract: Available statistics give indication that very often the freight transport business is a constant victim of crime. Previous research has proposed diverse security technical solutions and managerial strategies. However, anecdotal evidence suggests that these are not being implemented. This investigation aims to identify what factors may influence transport security. The study undertakes an exploratory approach to identify potential factors influencing transport insecurity. Thereafter, research hypotheses are formulated and tested by means of a survey study and multivariate techniques. Findings show that services differentiation and freight rates increments, JIT deliveries and insurance demand/supply behavior may influence the security level of transport companies. Highlights: Factors differentiating how transport companies manage security, importance of policy actions.